Organizational and economic basis for the development of industrial tourism in the Dnipropetrovsk region (Economics and region, 2021)
The theoretical and methodological basis of the study are scientific developments by Ukrainian and foreign scientists associated with the rethinking of industrial heritage, prospects for industrial tourism, the study of industrial tourism as an important area of tourism in industrial regions; legislative and normative acts of Ukraine in this field, materials of specialized scientific conferences and symposiums.It is distinguished that industrial tourism is a promising and effective direction in the territorial aspect, in this regard, this type of tourism is proposed to be considered as a priority of regional policy in the field of tourism and development of industrial enterprises. Features of formation of system of organizational-economic and institutional conditions and factors of development of industrial tourism in the Dnipro area are considered. Regional concepts, target programs, projects on the formation and development of industrial tourism in the Dnipropetrovsk region are studied. There are substantiated and developed in the article the practical recommendations for public administration, stimulation and support of industrial tourism in the region, taking into account its interaction with other subsystems of tourism. Practical recommendations for the formation of an effective organizational and institutional system of industrial tourism development are formulated, which include the adoption of a comprehensive regional program for the development of industrial tourism, the creation of an integrated management system for industrial tourism development at the regional and municipal levels. The results of the study are the basis for organizational and economic development of industrial tourism, which can increase the competitiveness of the tourism industry in the region and enterprises offering industrial tours.
Keywords: industrial tourism; tourist enterprise; tourist services; regional programs of support; tourist infrastructure; industrial heritage; innovative production technologies